Comparison of Intraocular Pressure (IOP) Value Before and After Vitrectomy in Diabetic Retinopatic Patients - Arnila Novitasari Saubig; Fifin Luthfia Rahmi; Hesti Triwahyu Hutami (Faculty of Medicine, Universitas Diponegoro, Semarang, Indonesia, 2021)
Background: Diabetic retinopathy is one of the second highest complications of microangiopathy in Indonesia due to diabetes mellitus in the form of damage to retina of the eye and can cause blindness in adults. The management of diabetic retinopathy is done by operative measure, one of which vitrectomy. However, this procedure can lead to an increase in the value of intraocular pressure after surgery. In this study, analysis of differences in intraocular pressure values before and after vitrectomy was carried out in patients with diabetic retinopathy.Research Purpose: To know, compare, and analyze the intraocular pressure values before and after vitrectomy in patients with diabetic retinopathy.Method: The study design was an analytic observation with a study design cross-sectional. Sampling using method consecutive sampling obtained from medical record of 45 diabetic retinopathy patients who underwent vitrectomy at the RSND for the period July-December 2019. After the data was collected, the data were analyzed using the difference Wilcoxon rank test.Result: A total of 45 diabetic retinopathy patients underwent vitrectomy from medical records were dominated by 24 people aged >69 years and 26 female patients. The mean values of intraocular pressure before and one week after vitrectomy were 20.32 + 2.57 mmHg and 23.89 + 9.24 mmHg. The results showed that there was a higher intraocular pressure value after vitrectomy than before vitrectomy in diabetic retinopathy patients (p=0.021) or p,0.05